PENGARUH RISIKO OPERASIONAL, RISIKO KREDIT, DAN RISIKO LIKUIDITAS TERHADAP PROFITABILITAS PERBANKAN KONVENSIONAL DI INDONESIA - Balgis Annisa Putri, (2022)
Profitability is the bank's ability to earn a profit within a certain period of time. Profitability development can be affected by different risks. The risks that occur can cause losses for the company. The purpose of this study was to determine the effect of operational risk, credit risk, and liquidity risk on the profitability of conventional banking in Indonesia. The sampling used was a saturated sample technique with a total of 43 conventional banks listed on the Indonesia Stock Exchange (IDX) for the 2018 - 2020 period. This study uses the Panel Data Regression Analysis technique as a hypothesis test with the use of E-views 12 and a significance level of 5% ( 0.05). The results of this study are that Operational Risk has no effect on Profitability, Credit Risk has a negative effect on Profitability, and Liquidity Risk has a positive effect on Profitability.